2012
DOI: 10.1128/mbio.00297-11
|View full text |Cite
|
Sign up to set email alerts
|

A Bilayer-Couple Model of Bacterial Outer Membrane Vesicle Biogenesis

Abstract: ABSTRACTGram-negative bacteria naturally produce outer membrane vesicles (OMVs) that arise through bulging and pinching off of the outer membrane. OMVs have several biological functions for bacteria, most notably as trafficking vehicles for toxins, antimicrobials, and signaling molecules. While their biological roles are now appreciated, the mechanism of OMV formation has not been fully elucidated. We recently demonstrated that the signaling molecule 2-heptyl-3-hydroxy-4-quinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
166
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(176 citation statements)
references
References 54 publications
5
166
0
Order By: Relevance
“…Several models, which are not necessarily mutually exclusive, describe the molecular mechanisms of OMV formation (8, 13, 26-29, 31, 33), but few studies have clarified which models apply to different species and/or growth conditions. These data have allowed us to refine the P. aeruginosa bilayer-couple model (31) for OMV biogenesis through demonstration that OprI reduces PQS-mediated OMV formation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several models, which are not necessarily mutually exclusive, describe the molecular mechanisms of OMV formation (8, 13, 26-29, 31, 33), but few studies have clarified which models apply to different species and/or growth conditions. These data have allowed us to refine the P. aeruginosa bilayer-couple model (31) for OMV biogenesis through demonstration that OprI reduces PQS-mediated OMV formation.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, OMV formation of the P. aeruginosa PA14 oprF, oprI, and oprL mutants was assessed as previously described using a spectrophotometric lipid assay (31). It is important to note that in strain PA14, oprI is reported to have a premature stop codon (TAA) at position ϩ139 relative to the ATG start codon (64); however, when we sequenced oprI from P. aeruginosa PA14, it was found that the codon encompassing position ϩ139 instead encodes glutamic acid (139T ¡ G), indicating that the open reading frame is intact.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lasI (PA1432) and rhlI (PA3476) genes encode the N-3-oxododecanoylhomoserine lactone (3-oxo-C12-AHL) synthetase (359,626) and Nbutyrylhomoserine lactone (C4-AHL) synthetase, respectively (360,362,627,628 (224). PQS also acts independently of MvfR to induce expression of the Fur regulon through its ability to bind iron (378,384) and membrane vessicle formation by inducing membrane curvature (576,632). PmpR (PA0964), a YebC member, negatively regulates MvfR ( Figure 6.2) (383).…”
Section: Ahl-mediated Qsmentioning
confidence: 99%